2022
DOI: 10.1371/journal.pone.0275638
|View full text |Cite
|
Sign up to set email alerts
|

Contrasted phylogeographic patterns of hydrothermal vent gastropods along South West Pacific: Woodlark Basin, a possible contact zone and/or stepping-stone

Abstract: Understanding drivers of biodiversity patterns is essential to evaluate the potential impact of deep-sea mining on ecosystems resilience. While the South West Pacific forms an independent biogeographic province for hydrothermal vent fauna, different degrees of connectivity among basins were previously reported for a variety of species depending on their ability to disperse. In this study, we compared phylogeographic patterns of several vent gastropods across South West Pacific back-arc basins and the newly-dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 76 publications
1
22
0
Order By: Relevance
“…Such a scenario may explain how individuals from the same species occur on both sides of the Atlantic and suggest that previously-isolated populations across the Caribbean Sea are currently experiencing a possible secondary contact with the arrival of rare but regular Barbados migrants in the US Atlantic margin waters (see below). Vicariant effects leading to concomitant species divergence at the community scale have also been documented in other deep-sea ecosystems, such as in the backarc-basins of the South West Pacific (Thaler et al, 2011;Thaler et al, 2014;Lee et al, 2019;Poitrimol et al, 2022; or along the East Pacific Rise (Plouviez et al, 2009;Matabos and Jollivet, 2019) in which taxa from several phyla…”
Section: A Shared Mitochondrial History Between Gigantidas and Bathym...mentioning
confidence: 80%
See 1 more Smart Citation
“…Such a scenario may explain how individuals from the same species occur on both sides of the Atlantic and suggest that previously-isolated populations across the Caribbean Sea are currently experiencing a possible secondary contact with the arrival of rare but regular Barbados migrants in the US Atlantic margin waters (see below). Vicariant effects leading to concomitant species divergence at the community scale have also been documented in other deep-sea ecosystems, such as in the backarc-basins of the South West Pacific (Thaler et al, 2011;Thaler et al, 2014;Lee et al, 2019;Poitrimol et al, 2022; or along the East Pacific Rise (Plouviez et al, 2009;Matabos and Jollivet, 2019) in which taxa from several phyla…”
Section: A Shared Mitochondrial History Between Gigantidas and Bathym...mentioning
confidence: 80%
“…harbor a dual symbiosis and relies more on sulfide-derived carbon (Prouty et al, 2016;Van Dover et al, 2003;DeLeo et al, 2022). Contrasted levels of spatial genetic sub-structuring and contemporary gene flow between species that went through the same vicariant effects have also been reported in relation with species-specific life history traits and dispersal abilities in several other oceanic regions (Plouviez et al, 2009;Thaler et al, 2014;Poitrimol et al, 2022;. In the Atlantic Ocean, two sympatric cold-water corals Desmophyllum pertusum and Madrepora oculata showed different post-glacial recolonization histories, most probably as a response to contrasted dispersal abilities and ecological requirements (Boavida et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
“…Biophysical models suggest that the Eastern regions (North Fiji, Futuna, Lau and Mangatolo) and Manus have no direct connectivity, and that Woodlark acts as a sink region for both ensembles (Matarai et al, 2016). Moreover, recent genetic data on several gastropod species also reported limited migration between the Eastern and Western domains (Castel et al, 2022; Tran Lu Y et al, 2022), and that Woodlark could act as a ‘stepping stone’ in the dispersal of S. tollmanni and other species (Poitrimol et al, 2022). In particular, Tran Lu Y (2022, p. 91) identified a strong genetic break between S. tollmanni populations indicating a complete absence of dispersal between the Manus basin and any site from the Eastern domain, while the two diverging S. tollmanni populations coexist (without admixture) at Woodlark site La Scala.…”
Section: Resultsmentioning
confidence: 99%
“…This has sparked renewed interest in establishing clear and stable descriptions of vent endemic fauna. Superficially similar or plastic morphology across clades makes it difficult to separate species lineages in some vent gastropods (Poitrimol et al 2022). Molecular data for several species in North Fiji and Lau and adjacent regions have shown that the species first recognised as new by Beck are indeed distinct, separate lineages without names (Poitrimol et al 2022;Schwarzpaul 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Superficially similar or plastic morphology across clades makes it difficult to separate species lineages in some vent gastropods (Poitrimol et al 2022). Molecular data for several species in North Fiji and Lau and adjacent regions have shown that the species first recognised as new by Beck are indeed distinct, separate lineages without names (Poitrimol et al 2022;Schwarzpaul 2002). Since Beck did recognise and describe these species, it is appropriate that his contributions are published and recognised.…”
Section: Introductionmentioning
confidence: 99%